A new algorithm for the registration of portal images to planning images in the verification of radiotherapy, as validated in prostate treatments - Jobse, Mark; Davelaar, Jaap; Hendriks, Emile; Kattevilder, Rob; Reiber, Hans; Stoel, Berend (Medical physics (Lancaster), 2003)
The manual verification of a radiotherapy treatment, where a portal image is matched onto a planning image, is very time consuming and subject to inter- and intraobserver variability. Therefore, a fully automatic matching procedure (image registration) is required. Existing automatic matching algorithms are confounded, however, by irrelevant information in the portal images (i.e., air in the intestines). Therefore, we have developed a new method, which is an extension of chamfer matching and uses, apart from the distance to the nearest edge, additional information on the correspondence of the gradient angle and magnitude of the edges, making the method less sensitive to confounding information in the images. To validate the automatic matching procedure in clinical practice, we applied the new method on 157 images of 29 randomly selected patients treated for carcinoma of the prostate. Three experts manually matched these images in consensus. Subsequently, the same observers assessed the results of the automatic registration. When regular chamfer matching is used for the fully automatic matching procedure, only 5% of the image pairs could be matched correctly, whereas the new method successfully registered 80% by using additional information on the angle of the edges. From the results of the validation study it can be concluded that a significant reduction in workload for the physicians and technicians can be achieved with this method.